Assessment of students’ satisfaction with nursing studies at the Faculty of Health Science, Warsaw Medical University. Pilot study - Gotlib, Joanna; Redel, Iwona; Stachacz, Grzegorz; Kaczyńska, Anna; Belowska, Jarosława; Panczyk, Mariusz (Medical Studies/Studia Medyczne, 2014)
Introduction:: The analysis of the opinions of students regarding their level of satisfaction with their studies constitutes one of the basic elements of global assessment of the quality of teaching at university-level schools. Aim of the research: : To analyse the assessment of satisfaction of students with the learning content and teaching methods in the field of nursing at the Faculty of Health Science, Medical University of Warsaw. Material and methods:: The study enrolled 200 full-time (ST) and part-time (NST) students, including 195 women (F) and 5 men (M). The mean age was 34 years and the questionnaire return rate was 55%. This was a voluntary and anonymous questionnaire study, with a questionnaire developed by the authors including 27 close-ended questions. The students received the questionnaire in the form of a link to an e-form. Statistical analysis was performed using Statsoft Statistica 10.0 (licensed to Medical University of Warsaw) and Mann-Whitney U test (significance level: p < 0.05). Results:: The majority of ST and NST students were satisfied with studying Nursing at Medical University of Warsaw. The vast majority of the study participants reported that the number of hours of lectures was sufficient, with ST students reporting thois significantly more often (p < 0.05). The students from both groups reported that the number of hours of seminars, classes and professional training sessions was sufficient (p = NS). The vast majority of the ST and NST students expressed a preference to choose theoretical classes and seminars on their own, in accordance with their interests and the character of their job. Compared to the ST students, the NST students significantly more often (p < 0.05) declared that the curriculum did not include a sufficient number of hours of the following courses: Contracting Health Benefits, Law in Health Protection and European Nursing. Conclusions: : Teaching in the field in Nursing met with the expectations of both ST and NST students from the study group. The mode of study may influence the expectations of students regarding the curriculum, learning content and organisation of the course, as well as the level of satisfaction with education received. In the study group, the part-time students had greater expectations regarding the structure of the curriculum and the learning content. The students’ level of satisfaction with learning should be assessed on a regular basis for continuous improvement and maintenance of high quality of teaching, and the study results should be introduced into the curriculum, learning content and teaching methods.